Robust and non-robust models in statistics - Klebanov, L. B. (Lev Borisovich), 1946-; Rachev, S. T. (Svetlozar Todorov); Fabozzi, Frank J. (New York : Nova Science Publishers)
Includes bibliographical references and indexes